1998
DOI: 10.1146/annurev.neuro.21.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Creb and Memory

Abstract: The cAMP responsive element binding protein (CREB) is a nuclear protein that modulates the transcription of genes with cAMP responsive elements in their promoters. Increases in the concentration of either calcium or cAMP can trigger the phosphorylation and activation of CREB. This transcription factor is a component of intracellular signaling events that regulate a wide range of biological functions, from spermatogenesis to circadian rhythms and memory. Here we review the key features of CREB-dependent transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
964
1
18

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,349 publications
(1,014 citation statements)
references
References 100 publications
(162 reference statements)
31
964
1
18
Order By: Relevance
“…They concluded that new neurons must be at a specific stage of maturation to be capable of supporting hippocampal-dependent learning. Previous studies have demonstrated a role for CREB in other forms of cellular and behavioral learning and memory (see Silva et al 1998). Localization of phospho-CREB during the critical period of granule cell maturation suggests that this transcription factor may play a role in deciding the functional fate of these new neurons (Figure 6).…”
Section: Colocalization Of Phospho-creb With Markers Of Maturing Neuronsmentioning
confidence: 99%
“…They concluded that new neurons must be at a specific stage of maturation to be capable of supporting hippocampal-dependent learning. Previous studies have demonstrated a role for CREB in other forms of cellular and behavioral learning and memory (see Silva et al 1998). Localization of phospho-CREB during the critical period of granule cell maturation suggests that this transcription factor may play a role in deciding the functional fate of these new neurons (Figure 6).…”
Section: Colocalization Of Phospho-creb With Markers Of Maturing Neuronsmentioning
confidence: 99%
“…Among the CREB-regulated genes are several genes important for neurotransmission and signalling (Impey et al, 2004). Moreover, CREB is involved in adaptative processes such as learning, memory (Silva et al, 1998), and opiodinduced addiction (Nestler, 2001). As the signalling pathways affected by lithium can also influence CREB, CREB-directed transcription could be a downstream mediator of lithium action.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the cyclic AMP cascade in memory processes has been recently evidenced. Genetic and pharmacological studies in mice and rats demonstrated that the cyclic AMP responsive element binding protein (CREB) is required for a variety of complex forms of memory, including spatial and social learning (Silva et al, 1998). The activation of the cyclic AMP-dependent protein kinase (PKA) induces long-term memory (Muller, 2000) and the inhibition of cyclic AMP phosphodiesterase reverses memory deĀ®cits in the radial arm maze task (Zhang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%